Hubungan antara Lama CPB dan Aortic Cross Clamp dengan Mortalitas dan Lama Rawat di ICU pada Pasien Pascaoperasi Katup Jantung di RSUP Dr. Sardjito - Anggraini, Diana; Widodo, Untung; Pratomo, Bhirowo Yudo (Jurnal Komplikasi Anestesi, 2018)
Background: CPB (cardiopulmonary bypass) results a non physiologic circulation and AOX (aortic cross clamp) causes a hypoxic condition of myocard. The length of CPB and AOX are probably factors that influence the ICU outcome after valvular heart surgery. Objective: To determine whether CPB and AOX time have significant effect on postoperative ICU length of stay (LOS) and ICU mortality. Methods: Data were collected from hospital medical record from period 2010 until 2016. After inclusion and exclusion 57 patients were analyzed for mortality and LOS in ICU. Results: Among 57 patients, 9 (15%) had ICU stay > 3 days, the mean+SD CPB was 119,2+32,5 min, AOX 92,7+27,7 min, while 7 (12,3%) had mortality in ICU, the mean+SD CPB was 113,7+37,3 min, AOX 79,3+36 min. Statistically showed that there were no correlation between duration of CPB and AOX with LOS and mortality in ICU, but we found that increased LOS in patient with comorbid (CHF+other) (p=0,019 OR 7,7 CI 95% 1,39-42,66) while ICU mortality increased with value of APACHE II (p=0,015 OR 1,69 CI 95% 1,11-2,58). Conclusion: There were no correlation of CPB and AOX time against ICU LOS and in mortality ICU, but preoperative factor (CHF+other) and postoperative factor (APACHE II score) respectively have a factor correlation.